2017
DOI: 10.1007/s12020-017-1283-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 2 (MMP-2) levels are increased in active acromegaly patients

Abstract: In this study, serum matrix metalloproteinase-2 level is increased in the active acromegaly patients and a threshold value in determining active disease was defined for serum matrix metalloproteinase-2 level. This study is the first to compare acromegaly patients having active or controlled disease in terms of matrix metalloproteinase-2 and matrix metalloproteinase-9 levels. The results need to be confirmed by a study that will be conducted in a larger patient group also including a healthy control group to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Indeed, in patients with risk factors for atherosclerosis or with established atherosclerosis, circulating monocytes have a pro-inflammatory phenotype, characterized by an increased cytokine production capacity [ 19 , 131 133 ]. It is suggested that this concept may also apply to acromegaly [ 118 , 134 137 ], since GH and IGF-1 have repeatedly been reported to impact on the immune system [ 20 , 138 , 139 ]. Moreover, circulating immune cells express GH and IGF-1 receptors [ 138 , 140 , 141 ], and macrophages and lymphocytes can produce IGF-1 [ 20 , 142 , 143 ].…”
Section: Inflammation In the Pathogenesis Of Atherosclerosis And Cvdmentioning
confidence: 99%
“…Indeed, in patients with risk factors for atherosclerosis or with established atherosclerosis, circulating monocytes have a pro-inflammatory phenotype, characterized by an increased cytokine production capacity [ 19 , 131 133 ]. It is suggested that this concept may also apply to acromegaly [ 118 , 134 137 ], since GH and IGF-1 have repeatedly been reported to impact on the immune system [ 20 , 138 , 139 ]. Moreover, circulating immune cells express GH and IGF-1 receptors [ 138 , 140 , 141 ], and macrophages and lymphocytes can produce IGF-1 [ 20 , 142 , 143 ].…”
Section: Inflammation In the Pathogenesis Of Atherosclerosis And Cvdmentioning
confidence: 99%
“…These fibrotic effects of GH are frequently context-specific and tissuespecific and not always in a direction that favours fibrosis. For example, an ECM-degrading endopeptidase, matrix metalloproteinase 2 (MMP2), is decreased after GH treatment of individuals with GHD 21 , but increased in patients with active acromegaly 22 . Likewise, TGFβ, a master regulator and promoter of fibrosis in multiple tissues, is regulated distinctly by GH in a tissue-specific manner.…”
Section: Gh and Other Fibrosis-promoting Factorsmentioning
confidence: 99%